Particle engineering of fenofibrate for advanced drug delivery system - Ramakant Joshi; Srajan Raje; Wasim Akram; Navneet Garud (SpringerOpen, 2019)
Abstract Background The goal of the current investigation was to formulate, evaluate co-crystal, and further design of solid unit dosage form of antihyperlipidemic BCS class II drug fenofibrate (FNO). Co-crystals composed of a structurally homogeneous crystalline material that contains two or more components in a definite stoichiometric amount helps in increasing yield, the capability to regulator polymorph fabrication, enhanced invention crystallinity. Ball milling method is used for co-crystal formulation, optimized via 32 full factorial design and characterized by saturation solubility, particle size analysis, Fourier transform infrared spectroscopy (FT-IR) study analysis, powder X-ray diffraction (PXRD) study analysis, surface morphology by scanning electron microscopy (SEM) study, flow properties, and ex vivo intestinal permeation study via non-everted rat intestinal sac model. Furthermore, optimized batch compressed into tablets is evaluated for disintegration time, hardness, friability, in vitro drug release study and stability study. Results It demonstrated that co-crystal formulation FNOCC7 shows higher saturation solubility 0.3874 ± 2.82 g/ml with less particle size 221.231 ± 0.456 nm, FT-IR spectra confirmed significant structural alterations in the formulation indicating the hetero-molecular interaction, the presence of hydrogen bonding had occurred in the co-crystals, PXRD spectra of formulation determined by the increase in the crystalline nature. FNO co-crystals show flux (F) and permeability coefficient (P app) 0.322 ± 0.068 μg/min, 5.38 ± 0.093 cm/min respectively increased compared to the pure drug makes in an enhancement of solubility as well as the bioavailability of BCS class II drug. Conclusions The solubility and dissolution percentage of FNO can be improved by the utilization of Co-crystal of FNO with PEG 4000. The solubilization impact of PEG 4000 might be contributed because of the decrease of molecule conglomeration of the drug presence of crystallinity, expanded wettability, and dispersibility; pharmaceutical co-crystals speak to a beneficial class of crystal form with regard of pharmaceuticals.